Air pollutants and SARS-CoV-2 in 33 European countries. - Lembo, Rosalba; Landoni, Giovanni; Cianfanelli, Lorenzo; Frontera, Antonio (Acta Biomedica Atenei Parmensis, 2021)
Background and aim: A potential correlation between severe acute respiratory syndrome coronavirus 2 and air pollution has been suggested in some nationwide studies. It is not clear whether air pollution contributes to the spread of SARS-CoV-2 and to increase mortality. Methods: Data on COVID-19 incidence, mortality rate, air pollution, and greenhouse gas element of 33 European countries were extracted from public available databases and analysed with Pearson correlation analysis for the overall population and normalizing for the population over 65 years. Results: Air pollutant agents such as particulate matter <10µm (PM10), particulate matter <2.5µm (PM2.5), ammonia (NH3), sulphur dioxide (SO2), non-methane volatile organic compounds (NMVOCs), nitrogen dioxide (NO2) and greenhouse gas elements recorded showed a remarkable correlation with cumulative positive number of SARS-CoV-2 cases and with cumulative number of COVID-19 deaths. PM2.5 (r = 0.68, p-value = 0.0001 for cumulative positive cases; r = 0.73, p-value <0.0001 for cumulative deaths) and nitrogen oxides (r = 0.85, p-value <0.0001 for cumulative positive cases; r = 0.70, p-value 0.0001 for cumulative deaths) were among the pollutant agents with the strongest correlation for both positive cases and deaths. Conclusions: High levels of pollution in European countries should be considered a potential risk for severe COVID-19 and SARS-CoV-2-related death.